2021
DOI: 10.1097/inf.0000000000003057
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and Respiratory Syncytial Virus Coinfection in Hospitalized Pediatric Patients

Abstract: was gradually tapered over 2 weeks then stopped; Sildenafil and Furosemide were stopped before discharge on day 34. At discharge, the baby was exclusively breast-feeding, neurologically stable, and had normal echocardiographic findings. He was well at followup after 7 days and at age 2 months; his declining antibody titers (Table 1) suggested transplacental transfer.In view of the positive anti-SARS-CoV-2 IgG antibodies in both baby and mother, transplacental transfer of maternal antibodies was considered to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 9 publications
0
24
1
Order By: Relevance
“…Several studies have recently reported the co-detection of SARS-CoV-2 with additional respiratory viruses in co-infected children and adults [ 3–5 ]. However, conflicting results were found in terms of clinical relevance [ 6 , 7 ]. Questions remain regarding the impact of co-infections on virus replication and disease severity and the mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently reported the co-detection of SARS-CoV-2 with additional respiratory viruses in co-infected children and adults [ 3–5 ]. However, conflicting results were found in terms of clinical relevance [ 6 , 7 ]. Questions remain regarding the impact of co-infections on virus replication and disease severity and the mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%
“…Concordant with the results of previous studies [14,18,21], RSV, HRV, and influenza were commonly detected in this study. Coinfection with RSV is associated with a longer length of stay [22]. HRV with a long period of viral shedding and environmental resistance [23] has been associated with higher morbidity rather than mortality, causing an economic burden [24].…”
Section: Discussionmentioning
confidence: 99%
“…Alvares 11 compared children with solely SARS-CoV-2 infection versus SARS-CoV-2/RSV coinfection and demonstrated longer hospitalizations in the coinfection group. Here, coinfection rates of SARS-CoV-2 were low, as reported in other studies 2 , 9 , 12 .…”
Section: Discussionmentioning
confidence: 99%